The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1177/1078155220922602
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic penile squamous cell carcinoma with dramatic response to combined checkpoint blockade with ipilimumab and nivolumab

Abstract: Introduction Prognosis for patients with lymph node positive or metastatic penile squamous cell carcinoma remains poor. Chemotherapy with paclitaxel, ifosfamide, and cisplatin (TIP regimen) is recommended as a first-line option in this cohort of patients. No standard preferred subsequent-line therapy exists for patients with relapsed or refractory penile carcinoma following TIP chemotherapy. Molecular pathogenesis of penile cancer can be subdivided into human papilloma virus-dependent and human papilloma virus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 19 publications
0
12
1
Order By: Relevance
“…Unlike in our study, simultaneous blockade of CTLA-4/CD80 and PD-1/PD-L1 axes has been more efficient than a single therapy in several studies [48][49][50]. Paradoxically, anti-PD-L1 administered as a single therapy may enhance CTLA-4/CD80-mediated immunosuppression in some patients due to the disruption of the tumor-suppressive CD80 and PD-L1 in cis interaction [9].…”
Section: Discussioncontrasting
confidence: 64%
“…Unlike in our study, simultaneous blockade of CTLA-4/CD80 and PD-1/PD-L1 axes has been more efficient than a single therapy in several studies [48][49][50]. Paradoxically, anti-PD-L1 administered as a single therapy may enhance CTLA-4/CD80-mediated immunosuppression in some patients due to the disruption of the tumor-suppressive CD80 and PD-L1 in cis interaction [9].…”
Section: Discussioncontrasting
confidence: 64%
“…In addition to significant responses from PD-1 and PD-L1 blockade, the consideration for combination ICB using PD-(L)1 and CTLA-4 inhibition has shown promise despite limited data, including a case report in a patient with metastatic penile cancer refractory to TIP, who had near resolution of large inguinal mass after two treatment cycles of nivolumab and ipilimumab. 102 An important ICB approval from a genomic standpoint was KEYNOTE 158, a multicohort phase II study of Pembrolizumab for advanced non-colorectal unresectable or metastatic cancers, that are MSI-H or mismatch repair-deficient (dMMR) tumors, and that have progressed following prior treatment without satisfactory alternative. Among the 233 enrolled patients, 27 tumor types were represented.…”
Section: Novel Therapeutic and Sequencing Approachesmentioning
confidence: 99%
“…Conversely, a report of a Phase II trial conducted in various rare malignancies showed that pembrolizumab was not capable of providing any benefits in two patients with microsatellite-stable PCa, while a durable response was obtained in a single man with a microsatellite instability high tumor [ 14 ]. Combination of anti-CTLA-4 agent ipilimumab and anti-PD-1 agent nivolumab administered at standard doses was associated with a prominent response in a patient refractory to paclitaxel, ifosfamide and cisplatin who was selected for treatment with ICIs on the grounds of the results of extensive molecular analysis showing high PDL-1 expression, microsatellite instability and tumor mutational burden, as well as alterations in DNA mismatch repair genes [ 15 ]. Conversely, in a single-arm, multicohort, Phase II trial, assessing nivolumab and ipilimumab in patients with advanced rare genitourinary cancers not selected on the grounds of any molecular biomarker, only two of five patients evaluable for radiological response showed stable disease [ 16 ].…”
mentioning
confidence: 99%